WEB-based bidirectional subject-selection system for graduation thesis - Zhenguo Chen; Liqin Tian; Dongyan Li; Zhen Peng; Xiaoju Wang (2010 3rd IEEE International Conference on Computer Science and Information Technology, 2010)
In this paper, by analyzing the deficiency and insufficient of subjects-selection in traditional graduate design, put forward to reform the process of subjects-selection in graduate thesis by application of web, propose an constructive programs of bidirectional subjects-selection system for graduation thesis. Bidirectional subjects-selection system for graduation thesis emphasizes the students-centered conception and is important to improve quality of graduation thesis. This software is designed specially to meet the needs of subjects-selection requirement. It's based on web and using PHP language and MYSQL database. The system has the characteristics of attractive,convenient and stable. It also has realizes shown that bidirectional subjects-selection system for graduation thesis can greatly give higher efficiency and quality than the traditional method.